DIVERSIFIKASI KONSEP KEAGAMAAN MASYARAKAT JAWA DALAM PERSPEKTIF CLIFFORD GEERTZ - Fatwa, AH Fajruddin (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
This study focuses on formulating the concept of Javanese religious community from the perspective of Clifford Geertz, focusing on the trilogy of Santri, Priyayi, and Abangan. exposing to social Clifford Geertz historiography research method. It addresses how Geertz understood and depicted the typology of Javanese society, particularly in the realm of religiosity. Research finding shows Geertz’s significant contributions to understanding the typology of Javanese society, especially concerning religious matters. Despite its geographic limitation to Mojokuto, this study lays a solid foundation for subsequent research triggered by the trikotomy concept in Javanese society. Geertz’s research in Mojokutoalso effectively categorizes the Javanese populace into three main groups: Abangan, Santri, and Priyayi. Moreover, Geertz adeptly describes the three dominant social structures in Java: markets, villages, and governmental bureaucracies. Through comparative analysis, Geertz provides profound insights into the religious expressions among Abangan, Santri, and Islamic Priyayi communities.Geertz’s research not only enhances Mojokuto patterns of Javanese religious communities but also stimulates further inquiries in this field, contributing significantly to the development of studies on Javanese society and religion.